Diagnosis of pneumococcal pneumonia by psaA PCR analysis of lung aspirates from adult patients in Kenya. - Scott, J; Marston, E; Hall, A; Marsh, K (2003)
psaA is the gene encoding pneumococcal surface adhesin A (PsaA), a 37-kDa protein expressed on the surface of Streptococcus pneumoniae. PCR primers for psaA have been shown to amplify the target DNA sequence in all 90 serotypes of S. pneumoniae and in none of 67 heterologous pathogens and colonizing bacteria of the upper respiratory tract. Pathogenic bacteria identified in lung aspirate specimens cannot normally be dismissed as contaminants or colonizers, which limit the assay specificity of other respiratory tract specimens. psaA PCR analysis was evaluated in 171 lung aspirates from Kenyan adults with acute pneumonia. The limit of detection was one genome equivalent. Sensitivity, estimated in 35 culture-positive lung aspirates, was 0.83 (95% confidence interval, 0.70 to 0.95). psaA PCR analysis extended the number of identifications of S. pneumoniae in lung aspirates from 35 on culture to 61 by both methods. Of 26 new pneumococcal diagnoses, 19 were corroborated by results of blood culture or urine antigen detection. Sequences of the PCR products from 12 positive samples were identical to the psaA target gene fragment. Using an internal control for the PCR, inhibition of psaA PCR was demonstrated in 17% (8 of 47) of false-negative specimens. The results of a control PCR for the human gene beta-actin suggested that false-negative psaA PCR results are attributable to problems of specimen collection, processing, or DNA extraction in 30% of cases (14 of 47). psaA PCR analysis is a sensitive tool for diagnosis of pneumococcal pneumonia in adults.